điều kiện \(x\ge0;x\ne9;x\in Z\)
\(P=\dfrac{\sqrt{x}+1}{\sqrt{x}-3}=\dfrac{\sqrt{x}-3+4}{\sqrt{x}-3}=1+\dfrac{4}{\sqrt{x}-3}\)
ta có :\(\dfrac{\sqrt{x}+1}{\sqrt{x}-3}\) nguyên \(\Leftrightarrow\dfrac{4}{\sqrt{x}-3}\) nguyên
\(\Leftrightarrow\) \(\sqrt{x}-3\) là ước của \(4\) là \(\pm1;\pm2;\pm4\)
ta có : * \(\sqrt{x}-3=1\Leftrightarrow\sqrt{x}=4\Leftrightarrow x=16\left(tmđk\right)\)
* \(\sqrt{x}-3=-1\Leftrightarrow\sqrt{x}=2\Leftrightarrow x=4\left(tmđk\right)\)
* \(\sqrt{x}-3=2\Leftrightarrow\sqrt{x}=5\Leftrightarrow x=25\left(tmđk\right)\)
* \(\sqrt{x}-3=-2\Leftrightarrow\sqrt{x}=1\Leftrightarrow x=1\left(tmđk\right)\)
* \(\sqrt{x}-3=4\Leftrightarrow\sqrt{x}=7\Leftrightarrow x=49\left(tmđk\right)\)
\(\sqrt{x}-3=-4\Leftrightarrow\sqrt{x}=-1\left(vôlí\right)\)
vậy \(x=16;x=4;x=25;x=1;x=49\)